2005
DOI: 10.1038/sj.cr.7290295
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes in virus-associated human cancers

Abstract: Epigenetics of human cancer becomes an area of emerging research direction due to a growing understanding of specific epigenetic pathways and rapid development of detection technologies. Aberrant promoter hypermethylation is a prevalent phenonmena in human cancers. Tumor suppressor genes are often hypermethylated due to the increased activity or deregulation of DNMTs. Increasing evidence also reveals that viral genes are one of the key players in regulating DNA methylation. In this review, we will focus on hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 86 publications
(85 reference statements)
1
77
0
1
Order By: Relevance
“…DNA methylation is one of the strategies that some viruses use to avoid detection by the immune system (Butel, 2000;Verma et al, 2007); specifically, the deregulation of DNMT family members has been proposed as one of the mechanisms that modulate gene expression in these interactions (Li et al, 2005). Therapy with demethylating agents in this kind of pathology has not yet been used against solid tumors in vivo, but for example, DNMT3B inhibitors could potentially be useful in HCC (Park et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is one of the strategies that some viruses use to avoid detection by the immune system (Butel, 2000;Verma et al, 2007); specifically, the deregulation of DNMT family members has been proposed as one of the mechanisms that modulate gene expression in these interactions (Li et al, 2005). Therapy with demethylating agents in this kind of pathology has not yet been used against solid tumors in vivo, but for example, DNMT3B inhibitors could potentially be useful in HCC (Park et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…T antigens are largely responsible for these alterations, and may interact with HATs (p300 and CBP) to enhance or repress gene expression (DeCaprio, 2009), or may induce aberrant methylation, possibly mediated by DNMTs (McCabe et al, 2006), in host gene promoters in several tumor types (Li et al, 2005;Goel et al, 2006).…”
Section: Polyomaviruses: Sv40 Jcv Bkv and MCVmentioning
confidence: 99%
“…Apart from introducing genetic changes, the presence of some oncogenic viruses was found to be correlated with the aberrant methylation profile of multiple TSGs in human cancers. 61,62 It is nowadays likely that SV40 may activate an aberrant methylation pathway that affects multiples TSGs during lymphomagenesis; however, the molecular mechanism underlying SV40-related aberrant methylation is currently still unknown. Determining precisely how SV40 infection leads to aberrant hypermethylation of promoter genes in human cancers seems to be a key question to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and forty-two miRNAs were identified as differentially expressed in JFH-1 HCV-infected and UV-inactivated HCV-infected Huh7.5.1 cells. Increased levels of miR-181a, miR-210 and miR-221 were observed in JFH1-infected Huh7.5.1 cells; and miR-455-3p slightly suppressed HCV propagation in vitro; as compared to UV-inactivated control cells [71]. Virus entry assays demonstrated that overexpression of miR-923 or inhibition of miR-149*, miR-373*, miR-638, miR-888, miR-940, miR-1181 or miR-1234 enabled entry of HCV pseudoparticles.…”
Section: Roles Of Mirnas In Virus-induced Hccmentioning
confidence: 96%